Are There Trigger Points in the Spastic Muscles? Electromyographical Evidence of Dry Needling Effects on Spastic Finger Flexors in Chronic Stroke - Lu, Zhiyuan; Briley, Amy; Zhou, Ping; Li, Sheng (Frontiers in Neurology, 2020)
The purpose was to examine the immediate effects of dry needling to spastic finger muscles in chronic stroke. Ten chronic stroke patients with spasticity in finger flexors participated in this experiment. Dry needling to the flexor digitorum superficiali (FDS) muscle was performed under ultrasound guidance for about 30 seconds (about 100 times). Clinical assessment and intramuscular needle EMG readings were made before and immediately after dry needling. Immediately after needling, the FDS muscle was felt less tight to palpation and the proximal phalangeal joint rested in a less flexed position (p=0.036). The MAS score decreased for FDS (p=0.017) and flexor digitorum profundus (FDP) (p=0.029). Motor unit action potential (MUAP) spikes decreased from 41.6±5.5 spikes/sec to 6.7±2.2 spikes/sec (p=0.002), an 84% reduction after dry needling. However, the pre-needling spike frequency was not correlated to MAS or resting position of the FDS muscles. Dry needling to the spastic finger flexors leads to immediate spasticity reduction, increased active range of motion, and decreased frequency of motor unit spontaneous firing spikes. The results suggest that there possibly exists latent trigger points in spastic muscles and they contribute partly to spastic hypertonia of finger flexors in chronic stroke.